Dose-Sparing Intradermal DTaP-sIPV Immunization With a Hollow Microneedle Leads to Superior Immune Responses - Zuo, Weilun; Li, Jingyan; Jiang, Wenwen; Zhang, Mengyao; Ma, Yan; Gu, Qin; Wang, Xiaoyu; Cai, Lukui; Shi, Li; Sun, Mingbo (Frontiers in Microbiology, 2021)
Dose-sparing intradermal (ID) vaccination may induce the same immune responses as intramuscular (IM) vaccination, which can increase vaccine supplies and save costs. In this study, rats were immunized with fractional-dose of Sabin-derived IPV combined with diphtheria-tetanus-acellular pertussis vaccine (DTaP-sIPV) intradermally with hollow microneedle devices called MicronJet600 and the vaccine immunogenicity and efficacy were evaluated and compared with those of full-dose intramuscular immunization. We tested levels of antibodies and the subclass distribution achieved via different immunization routes. Furthermore, gene transcription in the lung and spleen, cytokine levels and protection against Bordetella pertussis (B. pertussis) infection were also examined. The humoral immune effect of DTaP-sIPV delivered with MicronJet600 revealed that this approach had a significant dose-sparing effect and induced more effective protection against B. pertussis infection by causing Th1/Th17 responses. In conclusion, ID immunization of DTaP-sIPV with the MicronJet600 is a better choice than IM immunization, and it has the potential to be a new DTaP-sIPV vaccination strategy.